2007
DOI: 10.1007/s10346-007-0096-x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative approaches for analyses of a 100,000 m3 rock slide based on Barton–Bandis shear strength criterion

Abstract: Alternative approaches for analyses of a 100,000 m 3 rock slide based on Barton-Bandis shear strength criterion Abstract A data set was derived for the Åknes rock slope, Norway, with the main focus on deriving input parameters for the BartonBandis shear strength criterion. Back-calculations of a 100,000 m 3 rock slide were performed for evaluation of the data set. The limit equilibrium analysis showed that the joint roughness coefficient (JRC) has the greatest effect on the calculated safety factor of the slid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…17). Hencher (1976) (Kveldsvik et al 2008). Nicholson (1994) reports a variation in 12.5°for tests carried out on carefully prepared saw-cut, lapped surfaces of Berea sandstone, all suggesting that the recommendation of some lower ''limiting value'' of 28.5 to 31.5°may not be universally applicable.…”
Section: Estimating Shear Strength Using Empirical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17). Hencher (1976) (Kveldsvik et al 2008). Nicholson (1994) reports a variation in 12.5°for tests carried out on carefully prepared saw-cut, lapped surfaces of Berea sandstone, all suggesting that the recommendation of some lower ''limiting value'' of 28.5 to 31.5°may not be universally applicable.…”
Section: Estimating Shear Strength Using Empirical Methodsmentioning
confidence: 99%
“…Considerable scatter was reported and for one of the three joints a possibly bi-modal distribution of estimates was determined with the two centres of population at 8.9 and 17.9, perhaps reflecting different individual's perception of controlling roughness scale. Like any other stochastic parameter, considerable difficulties can occur when representing joint roughness with a single value JRC estimate, as clearly demonstrated by determinations for the Å knes landslide by workers from NGI and MIT (Kveldsvik et al 2008) where JRC measured for foliation joints at a 0.25-m scale ranged from 2.5 to 20 with a mean of 10.6. At a 1-m scale, JRC estimates covered the full possible range (from 0 to 20) with a mean of about 8 and standard deviation of *4.…”
Section: Estimating Shear Strength Using Empirical Methodsmentioning
confidence: 99%
“…Similar variability has perplexed other authors such as Nicholson (1994) who found that friction angles for saw-cut Berea Sandstone in direct shear tests varied by 12.5°despite great attention to sample preparation and reproducibility. Kveldsvik et al (2008), in their investigations of the Å knes rock slope, found that the ''basic friction angle'' derived from tilt testing of core varied between 21°and 36.4°.…”
Section: Textural Interlockingmentioning
confidence: 98%
“…[50] (Figure 4). More information about the rock slope geological setting can be found in [51][52][53] and in [54], where the results of extensive field and non-field work activities are summarized, such as geological and geophysical investigations, numerical modelling, etc.…”
Section: Geological and Geomorphological Settingmentioning
confidence: 99%